Increased risk of cognitive impairment in patients with components of metabolic syndrome. Issue 36 (September 2016) - Tsai, Chia-Kuang; Kao, Tung-Wei; Lee, Jiunn-Tay; Wu, Chen-Jung; Hueng, Dueng-Yuan; Liang, Chih-Sung; Wang, Gia-Chi; Yang, Fu-Chi; Chen, Wei-Liang
Abstract : Abstract: The number of old adults with cognitive impairment or dementia is anticipated to increase rapidly due to the aging population, especially the number of patients with multiple chronic conditions or metabolic perturbation. Metabolic syndrome (Mets) is among the most hazardous risk factors for cardiovascular disease and is linked to a chronic inflammatory disease. We investigated the National Health and Nutrition Examination Survey (NHANES) database for the years 1999 to 2002 to explore the connection between Mets and cognitive decline. A total of 2252 NHANES (1999–2002)-registered individuals who were stroke-free and aged ≧60 years were enrolled in this study. This study surveyed the effects of the existence of diverse characteristics of Mets on the individuals' cognitive performances as measured with the digit symbol substitution test (DSST). The individuals with more features of Mets achieved lower DSST scores than those with fewer constituents of Mets ( P  < 0.001 for the trend) after adjustments for covariates. The β coefficients for the DSST scores of the participants with 1, 2, 3, and ≥4 features of Mets were −1.545, −3.866, −4.763, and −5.263, respectively. Cognitive decline was correlated with each of the constituents of Mets, which included high plasma glucose, elevated blood pressure, abdominal obesity, and decreased high-density lipoprotein cholesterol ( P  < 0.05 for the above factors), with the exception of high triglyceride levels ( P  > 0.05). Mets was positively associated with cognitive decline in individuals aged ≧60 years. The characteristics of Mets that were most strongly associated with cognitive decline were high plasma glucose and elevated blood pressure.